2020
DOI: 10.1016/j.jpedsurg.2020.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Development of pediatric surgical decision-making guidelines for COVID-19 in a New York City children's hospital

Abstract: During the COVID-19 pandemic, experience-based guidelines are needed in the pediatric population in order to deliver high quality care in a new way that keeps patients and healthcare workers safe and maximizes hospital resource utilization. Background: The COVID-19 pandemic has created an unprecedented strain on national health care resources, particularly in New York City, the epicenter of the outbreak in the United States. Prudent allocation of surgical resources during the pandemic quickly became essential,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 18 publications
0
20
0
1
Order By: Relevance
“…CDC guidelines and additional retrospective studies have suggested that sufficient protection is provided to healthcare workers through the use of these PPE measures. The most significant risk of transmission is through the interrupted practice of proper social distancing and universal masking behaviors [12] . At the time of this research letter, there are no reported cases of COVID-19 transmission from an infected pediatric patient to a healthcare worker.…”
Section: Discussionmentioning
confidence: 99%
“…CDC guidelines and additional retrospective studies have suggested that sufficient protection is provided to healthcare workers through the use of these PPE measures. The most significant risk of transmission is through the interrupted practice of proper social distancing and universal masking behaviors [12] . At the time of this research letter, there are no reported cases of COVID-19 transmission from an infected pediatric patient to a healthcare worker.…”
Section: Discussionmentioning
confidence: 99%
“… 18 Many countries were compelled to alter their surgical practices and even postpone many elective and semi-urgent surgical procedures. 16 , 17 At our centre, elective procedures had been postponed in order to decrease disease transmission and conserve resources. This allowed us more flexibility in order to decrease the number of staff coming into the hospital on a daily basis, therefore reducing the risk of cross contamination and burnout.…”
Section: Discussionmentioning
confidence: 99%
“…Patients whose treatment had been postponed or cancelled were at risk, a peculiar and dangerous situation in which they could become potential collateral victims [25]. Urgent procedures, here defined as those to be resolved within one day to four weeks, were deferred as much as possible [27]. Shortly after the beginning of the pandemic, the dichotomy Fig.…”
Section: Peculiarities Affecting Pediatric Neurosurgerymentioning
confidence: 99%
“…Reduction in activity away from home may be a reasonable explanation for the drop in trauma referrals since parents and patients feared to go to the hospital [14,24]. The reduction of referral may also be ascribed to the lower number of trivial or ill-identified problems [28] and also the implementation of virtual consultations [27]. Notwithstanding, some centers noticed an increase in emergency services volume, yet without statistically significant differences [29].…”
Section: Peculiarities Affecting Pediatric Neurosurgerymentioning
confidence: 99%